The Role of Administration in Improving Administrative Services at SMA 2 Sungai Rumbai - Kirani, Mutia; Syoviana, Elvi; Andre, Lesis; Yunanda, B.R.E. (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This research is based on the vital role of administrative staff (TU) in supporting the smooth operation of schools, particularly in administrative services. Initial observation at SMAN 2 Sungai Rumbai revealed several issues such as disorganized filing systems, frequent errors in correspondence, and time constraints in completing administrative tasks. These issues prompted the researcher to investigate the extent to which administrative staff contribute to improving the effectiveness and efficiency of school administrative services.The purpose of this study is to examine how administrative services are implemented at SMAN 2 Sungai Rumbai, understand the roles carried out by the administrative staff, and identify their contributions in enhancing the quality of these services. Ultimately, the research aims to provide factual insights and solutions to the administrative challenges faced by the school. This study employs a descriptive qualitative approach. The subjects include the Principal, Head of Administration, and three administrative staff members of SMAN 2 Sungai Rumbai. Data collection techniques consist of observation, in-depth interviews, and documentation. Data analysis is based on the Miles and Huberman interactive model involving data reduction, data display, and conclusion drawing. No hypothesis is used due to the qualitative nature of the study.The results indicate that administrative services at SMAN 2 Sungai Rumbai are carried out according to indicators, including the manual recording of incoming and outgoing letters in an expedition book, document duplication using a printer due to the absence of a photocopy machine, orderly maintenance of the expedition book despite the lack of digital integration, and conventional archiving based on year and type of document. The role of administrative staff involves gathering documents from various sources, recording all incoming letters and important data, managing documents according to unit needs, duplicating letters with available tools, delivering documents to relevant parties, and storing archives in designated cabinets. In terms of improving administrative services, the administrative staff actively contribute by simplifying correspondence procedures, maintaining accuracy in recording, fostering teamwork, and organizing archives more systematically. Although challenges remain, such as limited human resources and inadequate facilities, the role of administrative staff continues to develop professionally with the support of the principal and a collaborative work culture.